Contract Conditions and BIM Use Effectiveness to Improve Project Performance - Francisco Villena Manzanares; Tatiana García-Segura; Eugenio Pellicer (Advances in Civil Engineering)
From a technological point of view, a huge potential can be found in building information modeling (BIM) in order to significantly improve the performance of a project. However, the literature review could not provide conclusive results on the impact that contractual practices may have on how effective BIM may result in technological terms, as well as outcomes within a project itself. The aim of this research is to determine the impact contractual conditions have on the link between BIM use effectiveness and the performance of a project. A self-administered survey was distributed to project design managers within architecture, engineering and construction engineering (AEC) firms. Using the partial least squares structural equation modeling (PLS-SEM) method, 92 answers were analyzed, finding contractual conditions to be mediating. These results show that appropriate conditions set in a contract with regard to handling BIM technology have a positive impact on the performance and outcomes of a project. The results, however, are only based on Spanish companies, meaning they may not necessarily be applied in global terms due to the cultural differences there may be within countries and continents, which should also be taken into account in the construction phase. Senior managers and policymakers could greatly benefit from the abovementioned findings with regard to improving contractual conditions in project design management in a BIM context, helping remove any source of conflict. It has been suggested by researchers that a gap has been found in BIM contractual practices literature, affecting not only BIM implementation but also project performance, thereby contributing to an improvement in BIM practices in construction contexts.